2022
DOI: 10.1111/ijfs.15549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasonic pretreatment on structural properties and biological activities of lupin protein hydrolysate

Abstract: This study examined how application of ultrasound pretreatment (UP) (400 W, 20 kHz for 5, 10 min) influenced the structural characteristics, molecular weight distribution, amino acid composition and biological activity of hydrolysate prepared from lupin protein using protamex enzyme. Circular dichroism (CD) and Fourier transform infrared (FTIR) techniques revealed changes in secondary structure after UP, while changes in molecular weight pattern were revealed by SDS-PAGE and MALDI-TOF analyses. Also, the cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
5
19
1
Order By: Relevance
“…The activity (%) of AH and TH obtained in this study against α -amylase and α -glucosidase was higher than the results obtained by Fadimu et al [ 31 ] from lupine protein hydrolysates using Protamex. According to Chandrasekaran and de Mejia [ 32 ], the inhibitory activity of α -glucosidase varies depending on the structure of the peptide, with IC 50 ranging from 1.78 mg/mL to 8.74 mg/mL for the isolated peptide from germinated chickpea protein hydrolysates.…”
Section: Resultscontrasting
confidence: 89%
“…The activity (%) of AH and TH obtained in this study against α -amylase and α -glucosidase was higher than the results obtained by Fadimu et al [ 31 ] from lupine protein hydrolysates using Protamex. According to Chandrasekaran and de Mejia [ 32 ], the inhibitory activity of α -glucosidase varies depending on the structure of the peptide, with IC 50 ranging from 1.78 mg/mL to 8.74 mg/mL for the isolated peptide from germinated chickpea protein hydrolysates.…”
Section: Resultscontrasting
confidence: 89%
“…There was no effect from beverages matrix, as well as functional supplements, which may suggest that a key role in this activity plays bioactive peptides driven by lentil proteins. It was previously shown in many studies, e.g., hydrolysate prepared from lupin protein using Protamex enzyme [57]. Such a mechanism is also supported by our previous study concerning protein digestibility, in particular, no effect of additives on this feature [23].…”
Section: Resultssupporting
confidence: 86%
“…The highest α-amylase inhibitory activity was observed in unfractionated hydrolysates generated using alcalase (ACT) (IC50 value = 1.66 mg/mL), followed by unfractionated hydrolysates from flavourzyme (FCT) (IC50 value = 1.98 mg/mL). This result is in accordance with previous studies which reported that hydrolysates generated using alcalase had significantly higher α-amylase inhibitory (lower IC50 value) ability than those prepared using flavourzyme, based on IC50 values [4,10].…”
Section: Inhibition Of the α-Amylase Inhibitory Activitysupporting
confidence: 93%